EXPERIMEN EXPERIMEN METODE AL-TAQLID WA AL-HIFDZ BERBANTUAN GESTURE DALAM PEMBELAJARAN MUFRADAT PADA KELAS X MA MIFTAHUL ULUM PUNTIR PURWOSARI - zuhrotul, mas'udah; Syaiful Rizal, Hasan (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
Based on the above, the researcher is interested in taking research with the title "experimentation of the application of the taqlid wa hifdzi method in mufrodat learning through gesture translation for class X students at Madrasah Aliyah Miftahul Ulum punter. This research uses a quantitative approach in which this is to find out the experimentation and the influence of the taqlid wa hifdzi method andResearch instruments used to input research data include tests and documentation. From the results of this study, the researchers obtained the result that with the values obtained, it can be concluded that there is a positive correlation between the dependent variable and the independent variable. This relationship is classified as a strong relationship, because the calculated r values range from 0.61 to 0.80. In the sense that the gesture-assisted al taqlid wa al hifdzi method experiment on mufrodat learning has a significant influence on mufrodat learning in class X MA. Miftahul Ulum Puntir – Purwosari.